2020
DOI: 10.3390/molecules25215094
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Insecticidal Activity of Benzylisoquinoline Alkaloids from Chilean Rhamnaceae Plants against Fruit-Fly Drosophila melanogaster and the Lepidopteran Crop Pest Cydia pomonella

Abstract: The Chilean plants Discaria chacaye, Talguenea quinquenervia (Rhamnaceae), Peumus boldus (Monimiaceae), and Cryptocarya alba (Lauraceae) were evaluated against Codling moth: Cydia pomonella L. (Lepidoptera: Tortricidae) and fruit fly Drosophila melanogaster (Diptera: Drosophilidae), which is one of the most widespread and destructive primary pests of Prunus (plums, cherries, peaches, nectarines, apricots, almonds), pear, walnuts, and chestnuts, among other. Four benzylisoquinoline alkaloids (coclaurine, laurol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…In previous work, the insecticidal effect of alkaloids with benzylisoquinoline skeletons obtained from the Chilean plants Talguenea quinquenervia , Peumus boldo , and Cryptocarya alba was studied. The results showed that these alkaloids possess acute and chronic insecticidal effects and the docking results show that these types of alkaloids present a good interaction with octopamine and ecdysone receptors showing a possible action mechanism [55] . On the other hand, cyclopeptide alkaloids have been reported to show different biological properties such as antibacterial activity, [56,57] antiplasmodial activity, [58,59] cytotoxicity, and recently as inhibitors of calmodulin‐induced activation of Ca 2+ ATPase [60] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous work, the insecticidal effect of alkaloids with benzylisoquinoline skeletons obtained from the Chilean plants Talguenea quinquenervia , Peumus boldo , and Cryptocarya alba was studied. The results showed that these alkaloids possess acute and chronic insecticidal effects and the docking results show that these types of alkaloids present a good interaction with octopamine and ecdysone receptors showing a possible action mechanism [55] . On the other hand, cyclopeptide alkaloids have been reported to show different biological properties such as antibacterial activity, [56,57] antiplasmodial activity, [58,59] cytotoxicity, and recently as inhibitors of calmodulin‐induced activation of Ca 2+ ATPase [60] .…”
Section: Resultsmentioning
confidence: 99%
“…The bioassays according to Quiroz‐Carreño et al [55] . Artificial diet was mixed with ethanol‐diluted alkaloids extracts at concentrations of 10, 50 and 100 ug ml −1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Quiroz-Carreño et al [ 118 ] reported that the benzylisoquinoline alkaloids coclaurine, laurolitsine, boldine and pukateine could interact with the heterodimer ecdysone receptor. Endocrine disturbance could also be found in non-emergent adults or deformed adults (adultoids), probably triggered by plant extracts containing phytoecdysteroids or terpenoids that act as JHAs [ 119 ].…”
Section: Botanical Insecticidesmentioning
confidence: 99%